Perfil soroepidemiológico da infecção pelo vírus da Hepatite B em pacientes e profissionais de hemodiálise no estado do Tocantins - Souza, Karla Prado de (2003)
A survey was conducted in the hemodialysis population of Tocantins state, Brazil, aiming to assess the prevalence of hepatitis B vírus (HBV) infection, to analyze associated risk factors, and also to investigate this vírus subtypes and genotypes distribution. All patients (n=100) and staff (n=20) were interviewed in the dialysis unit in Araguaína city. Blood samples were collected and serum samples screened for HBV serological markers by enzyme-linked immunosorbent assays (ELISA). Hepatitis B surface antigen (HBsAg) positive samples were tested for DNA-HBV by polymerase chain reaction (PCR) and also for serological subtyping of HBsAg by ELISA. Na overall prevalence of 45% (CI 95%: 35.5-54.8) was found for HBV infection in patients (4% were HBsAg/anti-HBs positive, 2% anti-HBc only and 39% had anti-HBc/anti-HBs markers). Among the 20 staff members, a HBV prevalence of 15% was found (3 were anti-HBc positive). Univariate analysis of risk factors to HBV infection showed that only shift of hemodialysis was associated with HBV positivity in patients. Among the 4 HBsAg-positive smaples, DNA-HBV was detected in 3 samples, which were identified as genotype A by restriction fragment length polymorphism (RFLP) analysis, and one of them could be subtyped as adw2. The present data show a low HBsAg prevalence rate. The finding that shift of hemodialysis was associated with HBV positivity suggests that nosocomial transmission may play a role in the spread of this vírus in the dialysis unit studied.